Significance of Serum Prostate Specific Antigen Levels in Evaluating Prostatic Lesions with Histopathological Correlation - Deshpande, Shruti Amit; Maimoon, Sabiha A; Mahore, Sadhana Devendra (Annals of Pathology and Laboratory Medicine, 2019)
Background: Prostate cancer is one of the commonest forms of cancer among men. Serum prostate specific antigen (PSA) used in the diagnosis of prostate cancer is also elevated in other benign and non-malignant diseases of prostate. Objectives: The objectives of the study were to determine the relationship of serum f(PSA) and t(PSA), its correlation with histopathological findings and to assess the PSA cut off variable in various pathological conditions of prostate with clinical relevance. Materials and methods: This study included 141 patients admitted for transurethral resection of prostate and 141 control cases. fPSA was determined on blood samples by sandwich enzyme linked immunosorbent assay and total PSA by Enzyme Linked Fluroscent Assay method. The samples were processed and stained with haematoxylin and eosin. Results: The mean t(PSA) values for benign, premalignant and malignant lesions were 10.3 ng/ml, 20.36 ng/ml and 75.92 ng/ml respectively. The mean serum fPSA values for benign, premalignant and malignant lesions were 3.2 ng/ml, 9 ng/ml and 13.2 ng/ml respectively. The cut off value for tPSA was 12.25 ng/ml and that of fPSA was 9.4ng/ml. The p value(<0.0001) was highly significant in determining premalignant and malignant lesions. Conclusion: Total PSA is raised in premalignant, malignant, inflammatory and benign neoplastic lesions of prostate. In cases where the t(PSA) values are between four - ten ng/ml, f(PSA) is useful marker in cases of malignancies, which were confirmed on histopathology.